The role of discoidin domain receptor 2 in the renal dysfunction of alport syndrome mouse model. Issue 1 (1st January 2021) - Sannomiya, Yuya; Kaseda, Shota; Kamura, Misato; Yamamoto, Hiroshi; Yamada, Hiroyuki; Inamoto, Masataka; Kuwazuru, Jun; Niino, Saki; Shuto, Tsuyoshi; Suico, Mary Ann; Kai, Hirofumi
Abstract: Alport syndrome (AS) is a hereditary glomerular nephritis caused by mutation in one of the type IV collagen genes α3/α4/α5 that encode the heterotrimer COL4A3/4/5. Failure to form a heterotrimer due to mutation leads to the dysfunction of the glomerular basement membrane, and end-stage renal disease. Previous reports have suggested the involvement of the receptor tyrosine kinase discoidin domain receptor (DDR) 1 in the progression of AS pathology. However, due to the similarity between DDR1 and DDR2, the role of DDR2 in AS pathology is unclear. Here, we investigated the involvement of DDR2 in AS using the X-linked AS mouse model. Mice were treated subcutaneously with saline or antisense oligonucleotide (ASO; 5 mg/kg or 15 mg/kg per week) for 8 weeks. Renal function parameters and renal histology were analyzed, and the gene expressions of inflammatory cytokines were determined in renal tissues. The expression level of DDR2 was highly elevated in kidney tissues of AS mice. Knockdown of Ddr2 using Ddr2 -specific ASO decreased the Ddr2 expression. However, the DDR2 ASO treatment did not improve the proteinuria or decrease the BUN level. DDR2 ASO also did not significantly ameliorate the renal injury, inflammation and fibrosis in AS mice. These results showed that Ddr2 knockdown by ASO had no notable effect on the progression of AS indicating that DDR2 may not be critically involved in AS pathology. This finding may provide useful information and further understanding of the role of DDRs in AS.